Characteristic of Posterior Capsular Opacification (PCO) in Dr. Mohammad Hoesin General Hospital: A Retrospective Study - Gina Sonia Fensilia Yolanda; Allie Solahuddin (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2022)
Introduction: Posterior Capsular Opacity (PCO), also called